The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1590/1806-9282.65.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed ovarian cancer - diagnosis using 18F-FDG PET/CT; 4.

Abstract: The information provided through this project must be assessed and criticized by the physician responsible for the conduct that will be adopted, depending on the conditions and the clinical status of each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…They have become more accessible since development of GCIG criteria and RECIST and used in clinical practice but not routinely adopted in clinical trials. 18 F-FDG PET/CT has been shown to be more sensitive and specific when compared with CT scans, 91% versus 84% and 91% versus 65% [ 22 ], respectively. Early detection of PD with 18 F-FDG PET/CT is particularly important for consideration of SCR, since recent studies have reported improved survival when complete resection could be achieved [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have become more accessible since development of GCIG criteria and RECIST and used in clinical practice but not routinely adopted in clinical trials. 18 F-FDG PET/CT has been shown to be more sensitive and specific when compared with CT scans, 91% versus 84% and 91% versus 65% [ 22 ], respectively. Early detection of PD with 18 F-FDG PET/CT is particularly important for consideration of SCR, since recent studies have reported improved survival when complete resection could be achieved [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT imaging with 18 F-FDG has a very high sensitivity rate of 85-100% for detection of recurrence in ovarian cancer (Figure 3), compared to CECT 18 F-FDG is more sensitive and more specific; with a sensitivity 91% vs. 84% for CECT and specificity of 91% vs. 65% (35).…”
Section: Suspected Recurrencementioning
confidence: 99%